Phytoplankton Community Structure And Coastal Water Quality Characteristics Of Manjung, Perak And Penang National Park, Penang - Halim, Muhammad Adlan Abdul (2014)
This study was carried out to determine the phytoplankton community structure and coastal water quality characteristics of Manjung, Perak and Penang National Park (PNP), Penang and to investigate the relationship between phytoplankton community and environmental parameters of the study areas. Five sampling stations adjacent to a thermal coastal power plant station (Sultan Azlan Shah Power Station) in Manjung and eight sampling stations surrounding the PNP were selected in this study. Collection of phytoplankton and water samples and measurement in-situ water quality parameters were done monthly from November 2009 to October 2010 during neap tide. A total of 101 phytoplankton species (36 genera) were identified in Manjung whereas a total of 71 species (33 genera) were identified in PNP. Bacillariophyta was the most common phytoplankton group found in Manjung (96.94%) and in PNP (95.63%), followed by Dinophyta (Manjung: 0.59%; PNP: 3.74%), Cyanophyta (Manjung: 0.32%; PNP: 0.57%) and Chlorophyta (Manjung: 2.15%; PNP: 0.06%). Odontella sinensis dominated MJ2 (near the inlet point of coastal power station; ISI: 6.28), MJ3 (near the outlet point of coastal power station; ISI: 5.18) and MJ4 (near the ash pond of coastal power station; ISI: 6.91) whereas MJ1 (reference site; ISI: 4.54) and MJ5 (near the mangrove areas; ISI: 6.90) were dominated by Pseudonitzschia heimii and Chaetoceros curvisetus respectively in Manjung.